Design of Digital Evidence Collection Framework in Social Media Using SNI 27037: 2014 - Adi Setya; Abba Suganda (JUITA : Jurnal Informatika, 2022)
Social media is a place that people use to socialize. In addition to socializing, social media is also often used as a crime medium by certain people. In the evidentiary process, law enforcers have the duty to present the evidence used by the suspect in committing his crime. The method used in collecting digital evidence from social media must have a clear scientific basis and guidelines. If the method used is not known as a theory or method in digital forensics, this will undermine all expert testimony and evidence presented in the court. Making a framework that can be recognized by all judicial administrators (judges, public prosecutors, attorneys for defendants, witnesses and defendants) is a solution that can be used as a standard so that the evidence process runs well. The framework that has been created by the researcher is an update from the previous framework. The framework design is made using the Composite Logic method. The composite logic method will collaborate with the Digital Forensics Investigation Models framework to produce a new framework. Based on existing data and facts, this research has produced a framework with better performance than the previous framework.